Age And Parity Toward Chronic Energy Deficiency (CED) Incident Of Pregnant Mother In Puskesmas Gaji - Utami, Aris Puji; Munir, Miftahul; Widyastuti, Endah Ratna (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
Pregnant mother with Chronic Energy Deficiency (CED) are pregnant women who suffer from a lack of calories and protein (malnutrition). Factors that influence CED pregnant women include age and parity. Age will affect the ability or experience of parents in providing nutrition, while parity is a woman who has given birth to a live (viable) baby. The purpose of this study was to determine the correlation between age and parity with the incidence of CED in pregnant women at the Gaji Kerek Health Center, Tuban Regency. The study used comparative analysis with a case and control approach. The sample are 80 people consisting of 40 pregnant women with CED and 40 without CED, sample was taken by simple random sampling technique. In this study, age and parity were the independent variables and chronic energy deficiency was the dependent variable. Data collected from secondary data were then analyzed by testing the contingency coefficient with a significance of α <0.05. The study showed most of the pregnant women who experienced CED (case group) occurred at the risk age and almost all of the pregnant women who did not experience CED (control group) occurred at the non-risk age. Most of the pregnant women who experienced CED (case group) and without CED (control groups) were multiparous. Based the result of this study, there is correlation between age and parity with the incidence of CED in pregnant mother (p-value = 0.000). Suggested to health workers at the Puskesmas Gaji to screen nutritional status as early as possible in their teens and carry out treatment to reduce the incidence of CED in pregnant women.